In-vitro anti-viral screening and cytotoxicity evaluation of copper-curcumin complex. (August 2013) - Chauhan, Gaurav; Rath, Goutam; Goyal, Amit K.
Abstract Multiple therapeutic activities attributed to curcumin deliver a challenge to explore its hidden qualities. Structural features set an opportunity to chelate metal ions and enhance the therapeutics in a specified direction. A metallo-herbal complex (MHco) of curcumin with copper (Cu2+) ions was synthesized and characterized by various spectroscopy techniques. It was screened for its antiviral activity and cytotoxicity. Studies revealed that the synthesized compound has good microbicidal activity and would be utilized for the development of vaginal microbicidal gel against viral infections.